A review of bio-based materials for oil spill treatment. (15th May 2018) - Doshi, Bhairavi; Sillanpää, Mika; Kalliola, Simo
Abstract: Being cost-effective, synthetic materials were initially used abundantly for the removal of oil. Gradually, however, awareness of the use of dispersants like Corexit, which makes water resources more toxic than oil, has changed the scenario for the treatment of spilled oil. The removal of spilled oil from water resources is still a very topical issue. An eco-friendly and sustainable approach towards the environment has introduced many low-cost, non-toxic and biodegradable materials along with different biomasses to make micro-to nano-sized materials, membranes, sponges/aerogel, etc. for the removal and recovery of oil from water resources. Additionally, the reusability of these materials after the recovery of oils has added one more step towards sustainability. This review comprises the work conducted by various researchers in the field of the removal and recovery of spilled oils using various biomasses and polymers, either in the form of sorbents or separators. Graphical abstract: Image Highlights: Low cost, non-toxic and biodegradable materials for oil spill treatment. Stability of Pickering emulsions by particles is more than surfactants stabilized emulsions. Mechanical removal of oil using gelators and aerogels. Gravity-driven separation of oil and water from their mixtures.